Studies on lantern Fish (Benthosema pterotum) I. Biochemical and Microbiological Investigations - GOPAKUMAR, K; RAMACHANDRAN NAIR, K G; VISWANATHAN NAIR, P G; NAIR, A LEKSHM; RADHAKRISHNAN, A G; NAIR, P RAVINDRANATHAN (Fishery Technology, 2017)
Lantern-fish, an under-utilised fish is present in abundance, all the year round intropical and sub-tropical waters. Biochemical and microbiological studies carried outon lantern fish, caught from the Gulfs of Oman and Aden are reported in this paper.